Constellating the Notion of the Port City: Echeverría, Weber, and Peripheral Territorial Development. (Res Gesta, 2025)
This work explores an analytical intersection between Esteban Echeverría, Max Weber, and developmentalist theory, based on their respective reflections on the livestock economy, foreign trade, and the territorial organization of the periphery. The aim is not to establish a direct lineage between these authors and traditions, but rather to reconstruct a shared field of inquiry that sheds light on the processes of subordinate integration of peripheral spaces into the global market. Through an analysis of a seldom-examined text by Weber —his study on rural workers in Entre Ríos— and fragments from Echeverría’s Segunda lectura a la Asociación de Mayo, the article investigates how elements such as land, livestock, labor, and exports become central to their diagnoses. Within this framework, it proposes a relational reading of the port-city category —not as a critical object, but as a conceptual figure whose emergence can be understood in dialogue with these antecedents. Finally, the study draws on contributions from developmentalism and the historiography of Miguel Ángel De Marco to articulate a perspective that allows us to understand the port-city as a form of territorial inscription of the global economy and as a persistent problem of peripheral organization.
Keywords: Developmentalism; Port-city; Echeverría; Weber